2011
DOI: 10.1190/1.3569600
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative interpretation of pulsed neutron capture logs: Part 1 — Fast numerical simulation

Abstract: Pulsed neutron capture (PNC) logs are commonly used for formation evaluation behind casing and to assess time-lapse variations of hydrocarbon pore volume. Because conventional interpretation methods for Σ logs assume homogeneous formations, errors may arise, especially in thinly bedded formations, when appraising petrophysical properties of hydrocarbon-bearing beds. There exist no quantitative interpretation methods to account for shoulder-bed effects on Σ logs acquired in sand-shale laminated reservoirs. Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Haley (1995) develops a log response equation to interpret Sigma logs in sand-shale laminated systems. Mimoun et al (2011) develop a rapid simulation method for cased-hole pulsed-neutron measurements and a 1D inversion scheme to estimate layer-by-layer formation Sigma. Both methods are based on thermal-neutron diffusion transport corrections and disregard the effect of mud-filtrate invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Haley (1995) develops a log response equation to interpret Sigma logs in sand-shale laminated systems. Mimoun et al (2011) develop a rapid simulation method for cased-hole pulsed-neutron measurements and a 1D inversion scheme to estimate layer-by-layer formation Sigma. Both methods are based on thermal-neutron diffusion transport corrections and disregard the effect of mud-filtrate invasion.…”
Section: Introductionmentioning
confidence: 99%
“…A similar situation of significant flux perturbations has been observed when modeling borehole sigma measurements across bed boundaries between sands and shales. Mimoun et al (2011) show that a diffusion model can be used to approximate such flux perturbations and hence improve the accuracy and reliability of borehole sigma models. Greenspan (1976) highlights several other formulations for calculation of related flux perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…These perturbation effects manifest themselves as higher-order terms in the Taylor's series expansion of the differential operator perturbation function (X-5 Monte Carlo Team, 2003). A diffusion correction method for simulating Sigma measurements in the presence of such perturbations was shown to improve accuracy across layers of dissimilar capture cross-sections (Mimoun et al, 2011). Methods that incorporate higher-order dependencies on borehole and environmental effects have also shown to improve accuracy in simulating gamma-gamma measurements (density and photoelectric factor) acquired in the presence of mudcake (Zhou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al (2009) documented the application of a neutron diffusion code (Butler et al, 1992) A similar situation of significant flux perturbations has been observed when modeling borehole sigma measurements across bed boundaries between sands and shales. Mimoun et al (2011) showed that a diffusion model can be used to approximate such flux perturbations and hence improve the accuracy and reliability of borehole sigma models. Greenspan (1976) …”
Section: Introductionmentioning
confidence: 99%